2019
DOI: 10.1002/anie.201903264
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Chiral Photonic Crystals

Abstract: Although it is well known that the amazing iridescent colors of the cuticle of beetles reflect the intricate nanoscale organization of bio‐fibers, artificial inorganic materials with comparable optical responses have not yet been synthesized from abiotic nanoscale building blocks. Such materials could find broad applications, including in circular polarizers, to generate circularly polarized luminescence, or in lasers. Herein, we describe a general method for the fabrication of biomimetic chiral photonic cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 41 publications
2
125
0
2
Order By: Relevance
“…used to scavenge ROS in vivo, therefore rescued the memory loss of mice with Parkinson's disease. 5) Chirality-based devices: As mentioned in Figure 2D, the layer-by-layer nanostructure of chiral NiMoO 4 •xH 2 O photonic crystals reported by Tang and co-workers [37] exhibited extremely large chiroptical activity (g max ≈ −1.6) with tunable features providing possibilities for chirality-based multifunctional devices with favorable optical, electrical, and magnetic properties.…”
Section: Applications and Perspectivesmentioning
confidence: 92%
“…used to scavenge ROS in vivo, therefore rescued the memory loss of mice with Parkinson's disease. 5) Chirality-based devices: As mentioned in Figure 2D, the layer-by-layer nanostructure of chiral NiMoO 4 •xH 2 O photonic crystals reported by Tang and co-workers [37] exhibited extremely large chiroptical activity (g max ≈ −1.6) with tunable features providing possibilities for chirality-based multifunctional devices with favorable optical, electrical, and magnetic properties.…”
Section: Applications and Perspectivesmentioning
confidence: 92%
“…Circular dichroism (CD) spectra of ZAS(180, 4.34)-T were measured and corrected to eliminate linear dichroism contributions using the reported protocol ( Figure S10). [24] Noteworthy are their exclusive negative CD signals with the wavelengths superimposed on the corresponding reflection bands (Figure 4 D, E). We also notice that the negative CD signals with the wavelengths coincided with corresponding reflection bands are universal in ZAS(180, 3.14)-80 and ZAS(239, 4.42)-80 ( Figure S11).…”
Section: Methodsmentioning
confidence: 99%
“…Tang and co-workers reported that acombination of selfassembly of NiMoO 4 •x H 2 Onanowires at the air-water interface and sequential deposition of their monolayers onto asolid surface resulted in formation of chiral photonic crystals (Figure 16), [88] which cannot be obtained by simple selfassembly at equilibrium. Assembled monolayers of colloidal NiMoO 4 •x H 2 On anowires were transferred onto as olid surface by Langmuir-Schaefer technique with intentional variation of the angle between the substrate and alignment direction of the nanowires.R epeating transfer with programmed variation of the relative deposition angle yielded ah ierarchical assembled structure with "twisted" layers.B y varying programmed structural designs,chiroptical responses from the resulting hierarchical structures could be easily tuned.…”
Section: Langmuir-blodgett Methodsmentioning
confidence: 99%
“…Tang and co‐workers reported that a combination of self‐assembly of NiMoO 4 ⋅ x H 2 O nanowires at the air–water interface and sequential deposition of their monolayers onto a solid surface resulted in formation of chiral photonic crystals (Figure ), which cannot be obtained by simple self‐assembly at equilibrium. Assembled monolayers of colloidal NiMoO 4 ⋅ x H 2 O nanowires were transferred onto a solid surface by Langmuir‐Schaefer technique with intentional variation of the angle between the substrate and alignment direction of the nanowires.…”
Section: Dynamic Assembly Involving Non‐equilibrium Processesmentioning
confidence: 99%